The Palgrave Handbook of Contemporary Kenya
XXIII, 483 p. 17 illus., 15 illus. in color.
Keywords: This volume is a bold attempt to address a comprehensive range of themes and issues relating to contemporary Kenya. It covers independent Kenya’s history, society, culture, economics, politics, and environment with great breadth and depth, comprising thirty-four chapters divided into three parts. Part I focuses on independence and the political economy of development, followed by Part II on environment, globalization, gender, and society. Part III examines the external context’s impact and implications for Kenya and the role of Kenya in the global political economy. Wanjala S. Nasong’o is Professor of International Studies at Rhodes College in Memphis, USA. Maurice N. Amutabi is Professor and Director of the Center for Science and Technology Studies at the Technical University of Kenya. Toyin Falola is Professor of History, University Distinguished Teaching Professor, and the Jacob and Frances Sanger Mossiker Chairin the Humanities at the University of Texas at Austin, USA. He is an honorary professor at the University of Cape Town, South Africa, and Extraordinary Professor of Human Rights at the University of the Free State, South Africa. .